Investigations into the origin of Einstein’s Sink - Pietrow, Alexander G.M. (Studium, 2019)
Einstein’s sink is a well-known object among physics and astronomy students at Leiden University. Stories about its origin have been passed down since it was moved to the large lecture room of the then newly built Oort Building in 1998. These stories claim that it was seen as an Einstein relic by the physics faculty, kept close to inspire young minds. After researching this story, I found that the sink is from the early 20th century and that it once stood in the large lecture room of the Kamerlingh Onnes Laboratory in Leiden. It is likely that at this time it was used by many scientists, including Einstein. However, my research also shows that the move from the KOL was done purely for financial reasons and had nothing to do with Einstein. It is possible that the story was made up to conceal this fact, creating a more appealing reason for these cutbacks. The sink is seen by many as a connection to Einstein’s and the university’s past and is liked for this fact and not the aforementioned legend.